Cervical necrotizing fasciitis: A case report and diagnostic experience - SONG Yujing; HU Chuanyu; TAO Xuejin; HUANG Chunming (Kouqiang hemian waike zazhi)
Cervical necrotizing fasciitis (CNF) is a highly dangerous infectious disease characterized by acute onset, rapid progression, and life-threatening severity. This article reports a case of CNF with acidosis in a diabetic patient caused by pericoronitis. Based on relevant research data, we thoroughly investigate the critical role of early diagnosis of CNF in the treatment process.